1970
DOI: 10.1590/s0071-12761970000100031
|View full text |Cite
|
Sign up to set email alerts
|

Glomevella cingulata (Stonem.) spauld. et v. schrenk. F. SP. phaseoli N.F., fase ascógena do agente causal da antracnose do feijoeiro

Abstract: O presente trabalho versa sobre a obtenção da fase perfeita de Colletotriohum lindemuthianum (Sacc. et Magn.) Scrib., dirimindo duvidas quanto a sua existência, suscitada pelo primeiro relato feito por SHEAR e WOOD (1913). Após ter encontrado duas linhagens heterotálicas que formaram ascosporos em acasalamentos, os autores estudaram alguns fatores ambientais que favorecem a reprodução sexuada, chegando-se as seguintes conclusões: peritecios se formaram sobre varios meios de cultura semi-sintéticos em cuja comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
2
15
0
2
Order By: Relevance
“…These values are in agreement with data described in the literature for the species C. truncatum derived from different hosts (Damm et al, 2009). The size of the ascopores of the strains G43-2 (21.84 x 7.69 µm) and G8-1 (22.59 x 9.3 µm) is in agreement with the data described previously in the literature for the species G. cingulata f. spp phaseoli (Castro et al, 2006;Souza et al, 2007); however, these values are higher than those reported by Kimati and Galli (1970) and Rodrigues-Guerra et al (2005).…”
Section: Discussionsupporting
confidence: 92%
“…These values are in agreement with data described in the literature for the species C. truncatum derived from different hosts (Damm et al, 2009). The size of the ascopores of the strains G43-2 (21.84 x 7.69 µm) and G8-1 (22.59 x 9.3 µm) is in agreement with the data described previously in the literature for the species G. cingulata f. spp phaseoli (Castro et al, 2006;Souza et al, 2007); however, these values are higher than those reported by Kimati and Galli (1970) and Rodrigues-Guerra et al (2005).…”
Section: Discussionsupporting
confidence: 92%
“…The underlying mechanism which produces such high levels of variability in this fungus is unclear. Although under laboratory conditions sexual reproduction has been observed for C. lindemuthianum (Kimati & Galli, 1970; Bryson, 1990), there is no direct evidence that the fungus undergoes sexual reproduction in nature. Occurrence of recombination via anastomosis and the parasexual cycle has also never been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic, morphogenetic and morphological studies have also been conducted with G. cingulata (Hüttig, 1935;Lucas, 1946;Wheeler et al, 1948;McGahen & Wheeler, 1951;Uecker, 1994), but isolates from common bean were not included until recently (Roca et al, 2000). The sexual form of C. lindemuthianum was not reported until 1970 when the formation of fertile perithecia through crosses in culture medium was observed (Kimati & Galli, 1970). Although genetic studies have been carried out with G. cingulata strains isolated from bean plants (Batista & Chaves, 1982;Bryson, 1990;Mendes-Costa, 1996, O'Sullivan et al, 1998, the only work with conventional cytogenetics in this genera was done in 1946 with strains isolated from Ipomea sp.…”
Section: Introductionmentioning
confidence: 99%